Feasibility of reducing the maximum shelf life of red blood cells stored in additive solution: a dynamic simulation study involving a large regional blood system. Issue 3 (4th December 2014) - Grasas, A.; Pereira, A.; Bosch, M.‐A.; Ortiz, P.; Puig, L.
<x xml:space="preserve">Abstract</x> Background and Objective Recent studies suggest that transfusion of old red blood cell (RBC)s, mainly those close to the 42‐day maximum shelf life (MSL), is associated with increased morbi‐mortality. Although there is no formal proof supporting a causal relationship, the precautionary principle asks for corrective interventions whenever they do not bring about other risks or unjustified costs. Here, we investigated the feasibility of reducing the MSL. Materials and Methods A trace simulation model was used to analyse the repercussions of several MSLs on a large regional blood system. The baseline model was fed with real input and output data from years 2009 to 2010 and validated against real inventory data. Shortage and outdate rates and inventory levels for each blood group were derived assuming 42‐, 35‐, 28‐, 21‐ and 14‐day MSLs, as well as several distribution rules and supply shocks (periods without blood collections). Results The model shows that MSL could be reduced to 28–35 days without major increases in the shortage or outdate rates, even after supply shocks. At the 21‐day MSL, the inventory capability to compensate supply shocks was severely reduced and translated into large shortage rates. The later were higher for group O and Rh‐negative RBCs as compared to group A and Rh‐positive, respectively. Conclusion Reductions of MSL to 28–35 days seem feasible and riskless and do not require major changes in the inventory management policies. Consequently, and giving preponderance to the precautionary principle, the Catalan Blood Agency has decided to reduce the MSL of RBCs from 42 to 35 days.